HUBUNGAN PENGETAHUAN LITERASI BENCANA TSUNAMI DENGAN KESIAPSIAGAAN MASYARAKAT DI WILAYAH PESISIR KELURAHAN TONDO - Sulistriani Cernang; Surianto; Kadek Bramdhika Ada (Universitas Widya Nusantara, 2026)
Indonesia is one of the countries with the highest disaster risk in the world due to its geographical and geological location. Located between three active tectonic plates and in the Pacific Rin of Fire, Indonesia is frequently hit by earthquakes, tsunamis, and volcanic eruptions. In addition, geographical factors and tropical conditions also cause hydrometeorological disasters such as floods, landslides, droughts, and tidal waves. Based on the World Risk Index, Indonesia ranks 38th out of 181 countries with the highest disaster risk. Central Sulawesi, especially Palu City, is one of the most vulnerable areas to earthquakes, tsunamis, and liquefaction, as recorded in the 2018 disaster that caused thousands of deaths and infrastructure damage. This study uses a quantitative study that applies an analytical descriptive methodology with a cross-sectional design. The study focused on using two questionnaires that aimed to see if there was a relationship between the two variables. Through the purposive sampling technique, 21 respondents were selected. results showed that 8 respondents (50.0%) had sufficient knowledge, 10 respondents (47.6%) had high preparedness. Bivariate analysis of both variables with the chi-square test obtained a value of p = 0.001 > alpha (0.05%), this study concluded that there is a relationship between Tsunami Disaster Literacy Knowledge and Community Preparedness in the coastal area of Tondo Village. There is a relationship between tsunami disaster literacy knowledge and community preparedness in the coastal area of Tondo Village.